An Update on the Management of Severe Cutaneous Drug Hypersensitivity Reactions - Gelincik, Aslı; Cavkaytar, Ozlem; Kuyucu, Semanur (Current Pharmaceutical Design, 2019)
Severe cutaneous drug hypersensitivity reactions involve of different mechanisms , some of which are life-threatening, such as Stevens-Johnson syndrome/toxic epidermal necrolysis, drug reaction with eosinophilia and systemic symptoms, acute generalized exanthematous pustulosis, generalized bullous fixed drug eruptions, serum sickness and serum sickness-like reaction and drug-induced vasculitis. These reactions may have substantial morbidity and mortality. In the past years, successive studies have provided new evidence regarding the pathogenesis of some of these severe reactions and revealed that underlying mechanisms are highly variable. Since these reactions have unique presentations and distinct pathomechanisms, the treatment methods and response rates might be different among various entities. Although supportive and local therapies are sufficient in some of these reactions, targeted immunosuppressive treatments and even mechanistic therapies such as plasmapheresis may be required in severe ones. However, there is still insufficient evidence to support the best treatment options for these patients since number of patients and large-scale studies are limited. In this review, conventional and new treatment options for severe cutaneous drug hypersensitivity reactions are presented in detail in order to provide the contemporary approaches to lessen the morbidity and mortality relevant to these severe iatrogenic diseases.
Keywords: Stevens-Johnson syndrome/toxic epidermal necrolysis